PERENCANAAN PENANGGULANGAN BENCANA MELALUI PENDEKATAN MANAJEMEN RISIKO - Didi Ahdi (REFORMASI, 2015)
The paradigm of disaster management in Indonesia are still emergency response, causing loss and damage is very large. For that needs to be changed the perspective of disaster management proactive, preventative in terms of disaster risk reduction that can be integrated into development planning. Methods of research used a qualitative approach with descriptive. Source of data derived from informants and documents. Data was collected through interviews and documentation. Data were analyzed using an interactive model of Miles and Huberman. The results showed that the disaster planning process through a risk management approach in Malang has been implemented although there is a stage that is not maximized, namely the identification of a new disaster risk mapping conducted regional / disaster-prone areas, the challenges ahead are the most priority is the synergy between disaster management regulations the regulation of development planning and the integration of DRR into development planning, while the alternative new ideas built upon the analysis of the factors that affect, the challenges ahead and the scientific study of coherent and competent.